2016
DOI: 10.14814/phy2.12643
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypoxia modulates expression of corticotropin-releasing hormone and arginine vasopressin in the paraventricular nucleus in the ovine fetus

Abstract: Maturation of the fetal hypothalamo–pituitary–adrenocortical (HPA) axis is critical for organ maturation necessary for the fetus to transition to the ex‐utero environment. Intrauterine stressors can hasten maturation of the HPA axis leading to fetal growth restriction and in sheep, premature birth. We have previously reported that high‐altitude mediated, long‐term‐moderate gestational hypoxia (LTH) during gestation has a significant impact on the fetal HPA axis. Significant effects were observed at the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Image analysis was performed using NIH ImageJ (Wayne Rasband, NIH) based in part on our published methods for quantification of neuronal numbers and structural volume in the CNS ([75, 76]). Original ICC or IF images were deconvoluted using ImageJ to separate individual colors (Red, green, blue) using identical parameters for each section (minimum, maximum, brightness), then for each color, converted to 16 bit greyscale images.…”
Section: Methodsmentioning
confidence: 99%
“…Image analysis was performed using NIH ImageJ (Wayne Rasband, NIH) based in part on our published methods for quantification of neuronal numbers and structural volume in the CNS ([75, 76]). Original ICC or IF images were deconvoluted using ImageJ to separate individual colors (Red, green, blue) using identical parameters for each section (minimum, maximum, brightness), then for each color, converted to 16 bit greyscale images.…”
Section: Methodsmentioning
confidence: 99%
“…The animals are at altitude from~40 days of gestational age (dGA) onward resulting in a maintained fetal PO 2 of 18 mmHg (normal~23-25 mmHg) at~140 dGA (term 148 dGA) (1,235,707). In marked contrast to this activational function of acute or prolonged hypoxia when initiated during the final third of gestation, the HPA axis of the fetus adapts divergently when development occurs under conditions of LTH from day 40 of gestation onward (235,709,712). Indeed, LTH fetal sheep do not deliver early and are not growth restricted, reflective of the ability to maintain normal basal cortisol production.…”
Section: Chronic Hypoxiamentioning
confidence: 99%
“…Although a non-invasive measure of fetal hypoxia would be useful, yet we are not aware of any known maternal biomarker of fetal hypoxia. Myers et al reported that arginin vasopressin (AVP) is a hormone produced by hypothalamus in fetal hypoxia [8]. Copeptin is a precursor of preprovasopressin which is secreted in an equimolar ratio to AVP in situations of high plasma osmolality, low blood pressure, and hypoxia [9].…”
Section: Discussionmentioning
confidence: 99%